The impact of a 60-minute swimming training on the quality of body posture and the level of balance in young adults - Aksamit, Dżesika; Sidor, Tomasz; Gądek, Adrian; Jankowicz-Szymańska, Agnieszka (Health Promotion & Physical Activity, 2019)
Introduction: Postural abnormalities are common in every age group. They often involve discomfort or pain. Unfortunately, specialist posture correcting body postures are almost exclusively for pre-school and school children. There is a widespread belief in the beneficial effects of swimming on the body posture. Some even think that swimming can replace corrective exercises. The aim of the study was to evaluate the changes in the quality of body posture and body balance under the influence of 60-minute intensive swimming training in people aged 20-22 years, whose level of swimming skills was determined as average. Material and methods: The study was conducted on a group of 9 people, students of the State Higher Vocational School in Tarnów. Ultrasonic device Zebris Pointer was used for three-dimensional assessment of body posture. The position of the shoulder and iliac girdle, the shape of the spine, the inclination of the sacrum bone and the inclination of the body in the sagittal and frontal plane were analyzed. The test was repeated before and after the one-hour lecture and before and after one-hour, intensive classes at the swimming pool. The results were developed in the Statistika v10 program. Descriptive statistics, non-parametric Friedman test and Kruskal posthoc test were used. The significance level α = 0.05 was assumed. Results: There was a statistically significant increase in pelvic rotation under the influence of swimming training. There was also a slight deterioration of the spine position in the frontal plane. Exercises improving swimming in the classic style did not affect the depth of thoracic kyphosis and lumbar lordosis. After 60 minutes spent in a relaxed sitting position, deepening thoracic kyphosis was observed. However, this change was not statistically significant. Conclusions: It is not recommended to treat swimming as a substitute for corrective gymnastics. Intensive swimming training can exacerbate existing body posture errors in people who are just improving their swimming technique.